Comparison of 5-megapixel cathode ray tube monitors and 5-megapixel liquid crystal monitors for soft-copy reading in full-field digital mammography. - Schueller G; Schueller-Weidekamm C; Pinker K; Memarsadeghi M; Weber M; Helbich TH; Schueller, Gerd; Schueller-Weidekamm, Claudia; Pinker, Katja; Memarsadeghi, Mazda; Weber, Michael; Helbich, Thomas H (European Journal of Radiology, 2010)
Purpose: To retrospectively compare the image quality, lesion detection, and the diagnostic efficacy of 5-megapixel (MP) cathode ray tube monitors (CRTs) and 5-MP liquid crystal display monitors (LCDs) for soft-copy reading in full-field digital mammography (FFDM). Materials and Methods: Informed consent was waived by the Institutional Review Board for the data analysis. A total of 220 cases were compared with two 5-MP (2048×2560 pixels) CRTs and two 5-MP (2048×2560 pixels) LCDs. Nine aspects of image quality (brightness, contrast, sharpness, noise, skin, fat, retromamillary space, glandular tissue, and detection of calcifications) were evaluated. In addition, the detection of breast lesions (mass, calcifications) and diagnostic efficacy, based on the BI-RADS classification, were correlated with histologic results (n=70) and follow-up (n=150). Results: Each aspect of the image quality was rated significantly better for 5-MP LCDs (p<0.05) compared to the 5-MP CRTs. With 5-MP CRTs, 31 masses and 119 calcifications were detected, compared to 30 and 121 with 5-MP LCDs. The differences in diagnostic efficacy between 5-MP CRTs and 5-MP LCDs were not significant (p=0.157) although 5-MP CRTs yielded two false-negative results. Both lesions were rated BI-RADS 3 with 5-MP CRTs. Both were invasive carcinomas at histology. The sensitivity, specificity, positive and negative predictive values, and accuracy were 0.966, 0.975, 0.933, 0.988, and 0.973 for 5-MP CRTs, compared to 1.0, 0.963, 0.903, 1.0, 0.973 for 5-MP LCDs. Conclusion: The image quality of 5-MP LCDs is significantly better than that of 5-MP CRTs for soft-copy reading in FFDM, based on histologic and follow-up correlation. However, lesion detection and diagnostic efficacy are comparable to 5-MP CRTs. The interpretation of the false-negative results suggests that the characterization of breast lesions with FFDM is not defined solely by the monitors, but is strongly influenced by the radiologist.